Montelukast Has no Impact on the Systemic Production of TGFβ-1 in Patients with Nasal Polyposis Associated with Aspirin Intolerance - Pezato, Rogério; Gregório, Luciano Lobato; Pérez-Novo, Claudina; Bezerra, Thiago Ferreira Pinto; Kosugi, Eduardo Macoto (International Archives of Otorhinolaryngology, 2020)
Introduction Nasal polyposis is a disease characterized by a mechanical dysfunction of the nasal mucosa, closely related to the unique makeup of its extracellular matrix, which develops as the result of an anomalous tissue remodeling process.Transforming growth factor beta 1 (TGF-β1) is reduced not only in the nasal polypoid tissue, but also in the plasma of aspirin-intolerant patients. These patients exhibit an imbalance in the production of eicosanoids characterized by an increase in leukotrienes. Thus, it is important that the relationship between the production of leukotrienes and TGF-β1 be assessed.Objective To evaluate the effects of the cysteinyl leukotriene (CysLT) receptor antagonist montelukast on the systemic production of TGF-β1 in patients with nasal polyposis, with or without concomitant aspirin intolerance.Methods The sample comprised 48 individuals with diagnosis of nasal polyposis and 15 healthy controls for comparison of the baseline TGF-β1 levels in the peripheral blood and after treatment with CysLT receptor antagonist montelukast in the nasal-polyposis group.Results There was no difference in the change in TGF-β1 levels after the treatment with montelukast in the subgroup of patients with polyposis and asthma (p = 0.82) and in the subgroup with polyposis, asthma, and aspirin intolerance (p = 0.51).Conclusion we found no impact of the therapy with a leukotriene receptor blocker on the production of TGF-β1, making the antileukotriene therapy a highly questionable choice for the treatment of nasal polyposis, particularly from the standpoint of seeking to modify the remodeling process in this disease.
Keywords: rhinosinusitis; airway; nasal polyposis; inflammation; allergy